Convective heat transfer of hybrid nanofluid flow in a cavity having vertical wavy sides - Al Kalbani, Khamis; Uddin, M. J. (Iraqi Journal of Science, 2025)
Future hydraulic thermal substances made of hybrid nanofluids have a lot of potentials to fulfill the strict applied thermal energy management specifications of cutting-edge heat flux tricks. Due to synergistic thermal effects and general hydrothermal characteristics, it is necessary to examine the enhanced heat-transfer properties of nanofluids based on hybrid nanomaterials in various advances for the thermal management of machines with advanced heat flux. In a variety of corrugated casings filled with water and a hybrid nanofluid, the effects of a horizontal magnetic field on natural convection heat transfer have been studied. Finite element techniques (FEM) have been employed to solve the generated dimensionless partial differential equations of the imposed nanofluids. On three distinct wave-shaped heated walls, the streamlines, heat flow, and average Nusselt number for the base fluid and the hybrid nanofluids were plotted and examined. The outcome demonstrates how the device’s undulating walls and magnetic field strength have a major impact on heat transfer and heat flow.